2013
DOI: 10.1002/eji.201242784
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral CD4+T‐cell tolerance is induced in vivo by rare antigen‐bearing B cells in follicular, marginal zone, and B‐1 subsets

Abstract: Summary B cells are efficient APCs when they internalize antigen via BCR-mediated uptake. Adoptively transferred antigen-presenting B cells can induce T-cell tolerance to foreign and self antigens; however, it is unknown whether endogenous B cells presenting self-peptides interact with naïve T cells and contribute to peripheral T-cell self-tolerance. Moreover, the relative abilities of mature B-cell subsets to induce T-cell tolerance have not been examined. To address these questions, we created a new mouse mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…This observation was consistent with that self-antigen-bearing B cells stimulated antigen-specific T cells proliferation in vivo 1338. B-cells-activated self-antigen-specific CD4 + T cells decreased proliferative capacity ex vivo 123940, and which unresponsiveness without association with Foxp3 expression13. Addition to self-antigens, genetically B cell-deficient mice had a defected tolerogenic response to antigen from the oral route or nasal route841.…”
Section: Discussionsupporting
confidence: 88%
“…This observation was consistent with that self-antigen-bearing B cells stimulated antigen-specific T cells proliferation in vivo 1338. B-cells-activated self-antigen-specific CD4 + T cells decreased proliferative capacity ex vivo 123940, and which unresponsiveness without association with Foxp3 expression13. Addition to self-antigens, genetically B cell-deficient mice had a defected tolerogenic response to antigen from the oral route or nasal route841.…”
Section: Discussionsupporting
confidence: 88%
“…B cells have both positive and negative effects on immune responses and autoimmune diseases . B cells can induce tolerance in CD4 + T cells, primarily by producing IL‐10 or other suppressive cytokines . B cells also function as regulatory cells, whereby a specialized subset of IL‐10‐producing B cells can inhibit immune responses and autoimmune diseases .…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49][58][59][60] B cells can induce tolerance in CD4 + T cells, primarily by producing IL-10 or other suppressive cytokines. 47,49,58,[61][62][63] B cells also function as regulatory cells, whereby a specialized subset of IL-10-producing B cells can inhibit immune responses and autoimmune diseases. 47,48,58,60,[63][64][65] However, in autoimmune diseases such as SAT that require B cells for their development, B cells function primarily as APC to initiate disease.…”
Section: The Function and Phenotype Of B -/-Treg Cells Is Altered By mentioning
confidence: 99%
“…Raimondi et al demonstrated that adoptive transfer of antigen-presenting B cells four times in a week lead to antigen-specific CD4 + T cells tolerance independent of naïve or activated B cells [ 60 , 61 ]. Antigen-presenting follicular B, marginal zone B, and B-1a cells rendered antigen-specific T cells hyporesponsiveness without Foxp3 + Treg cells induction [ 62 ]. One study reported that B cells contributed to Treg cells homeostasis and cooperated with Treg cells to ameliorate inflammation [ 63 ].…”
Section: Main Textmentioning
confidence: 99%